Effect of organic, conventional and mixed cultivation practices on soil microbial community structure and nematode abundance in a cultivated onion crop. (7th June 2013) - Reilly, Kim; Cullen, Eileen; Lola‐Luz, Theodora; Stone, Dorothy; Valverde, Juan; Gaffney, Michael; Brunton, Nigel; Grant, James; Griffiths, Bryan S
Abstract: BACKGROUND: Responses of the soil microbial and nematode community to organic and conventional agricultural practices were studied using the Teagasc Kinsealy Systems Comparison trial as the experimental system. The trial is a long‐term field experiment which divides conventional and organic agriculture into component pest‐control and soil treatment practices. We hypothesised that management practices would affect soil ecology and used community level physiological profiles, microbial and nematode counts, and denaturing gradient gel electrophoresis (DGGE) to characterise soil microbial communities in plots used for onion ( Allium cepa L.) cultivation . RESULTS: Microbial activity and culturable bacterial counts were significantly higher under fully organic management. Culturable fungi, actinomycete and nematode counts showed a consistent trend towards higher numbers under fully organic management but these data were not statistically significant. No differences were found in the fungal/bacterial ratio. DGGE banding patterns and sequencing of excised bands showed clear differences between treatments. Putative onion fungal pathogens were predominantly sequenced under conventional soil treatment practices whilst putative soil suppressive bacterial species were predominantly sequenced from the organic pest‐control treatment plots . CONCLUSION: Organic management increased microbial activity and diversity. Sequence data was indicative of differences in functional groups and warrants further investigation. © 2013 Society of Chemical Industry